Moisture diffusivity in mortars of different water–cement ratios and in narrow ranges of air humidity changes - Garbalińska, Halina; Kowalski, Stefan J.; Staszak, Maciej (International journal of heat and mass transfer, 2013)
The aim of this paper is to assess moisture diffusivity in a group of cement-based mortars of different water–cement ratios by different moisture contents. Five levels of moisture content equivalent to five narrow ranges of contiguous air humidity changes were considered. The effective (average) diffusion coefficients were estimated for these five moisture levels and the experiments covered mortars with three different water–cement ratios amounting to 0.50; 0.65; 0.80. The diffusion coefficients were determined by way of adjustment of the theoretical and experimental drying curves. The theoretical drying curves were determined from numerical solutions of linear diffusion equations with a constant (average) diffusion coefficient for a given narrow humidity range. The theoretical drying curves were correlated with those corresponding experimentally using the Levenberg–Marquardt modified iterative algorithm. The Gauss–Newton numerical method was used for a minimization problem by fitting the drying curves, and in this way the values of diffusion coefficients for the selected materials were determined.